PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KELURAHAN ANTASAN BESAR KECAMATAN BANJARMASIN TENGAH KOTA BANJARMASIN - Erna Suriyani; Muhammad Erfa Redhani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
This research aimed to know how the community participated in household wastemanagement in Antasan Besar urban village, Central Banjarmasin Subdistrict. The type of researchmethod used is descriptive research with a qualitative approach, while data collection wasperformed through observation, documentation, questionnaires, and interviews.The results showed that people's participation in household waste management was quite goodgiven how they disposed of their waste. Most people have thrown garbage in temporary landfills(TPS), although there is still a small percentage of residents who throw garbage carelessly in theneighborhood and the river, or even burn it even though there have been some regulations. Theirparticipation is quite good in gotong royong activities to clean the environment, but their initiativeto invite other residents to clean is still low. Participation in sorting organic and non-organic wasteand recycling waste is still low. They do not recycle because they do not know and understand howto recycle. In contrast, their participation in reusing goods for another use is quite high.Participation in giving suggestions and opinions to local governments regarding waste managementis still very low. The main obstacle for the community in Antasan Besar sub-district in overcomingthe problem of household waste is the infrastructure, namely the absence of public trash cans, thedistance from the temporary waste disposal site from the residence, and the short schedule forwaste disposal.The best step to take is to start waste management from each household, and to facilitate it, itis recommended to the authorized agency or community group to carry out activities: 1).Counseling on the negative impact of burning household garbage and disposing of waste carelesslyin residential areas or rivers; 2). counseling on the need for waste recycling, reusing/upcyclingtrash, and sorting organic and non-organic waste 3). carrying out learning skills of recycling andcomposting waste for the community; 4). assisting in the fulfillment of infrastructure facilities,especially organic and non-organic waste bins, 5) socialization of Banjarmasin City RegionalRegulation No. 21 of 2011 on The Management of Land / Cleanliness and Sanitation, including theprohibitions and sanctions in the regulation.